Dominējošā stāvokļa normu interpretācija konkurences tiesībās - Valaine, Vilma (Latvijas Universitāte, 2010)
Darba nosaukums ir „Dominējošā stāvokļa normu interpretācija konkurences tiesībās.” Darbs pamatā ir veikts Latvijas un Eiropas Savienības tiesību nozares ietvaros. Darba mērķis ir apzināt tiesu lomu dominējošā stāvokļa interpretācijā konkurences tiesību ietvarā no tiesību zinātnes skatu punkta. Censties noskaidrot faktorus, kas nacionālo tiesu līmenī traucē dominējošā stāvokļa normu interpretācijai privātajās tiesībās maksimālu efektīvu darbību. Darbs ir sadalīts četrās pamat nodaļās, kas sadalītas apakšnodaļās. Katra nodaļa sākta ar ievaddaļu, kurā tiek dots ieskats nodaļā aplūkotajos jautājumos un to saistību ar darba mērķiem. Katras nodaļas beigās ir dots būtiskāko nodaļā pausto atziņu kopsavilkums. Darbu noslēdz visa darba kopsavilkums un izmantoto informācijas avotu saraksts, kā arī pielikumi.

The topic of these Master Thesis is “Interpretation of the Concept of Dominant Position in the Competition Law”. The theses are part of studies in Latvia’s and European Union’s Law. The aim of these theses is to analyze the role of the courts in interpretation of the concept of dominant position in competition law from a scientific point of view and to identify the reasons that hinder efficient implementation of this concept at the national level. Mainly research, analytic and comparison methods are used throughout the work. At the beginning of the work the focus is on ascertainment of the term "dominant position in competition law" in writings of various authors and in the legislation. Further, interpretation of the freedom of competition and the concept of dominant position and the practice of the European Commission, European Court of Justice and the Council of Competition are analysed. The following sources were used in comparison of various adjudications related to dominant position in the field of competition rights: primary jurisprudential sources, such, as the judgments, secondary sources, like publications on problems in interpretation of the concept of dominant position by experts of law, as well as multiple the information gathered as part of internship at the Competition Council. From the legal theory point of view, this work acknowledges problems in incompleteness of interpretation of the competition rights in the field of the concept of dominant position. The thesis consists of four chapters each of which is divided into sub-chapters. Each chapter begins with an introduction to the issues discussed in the chapter and their connection with the aims of this work. At the end of each chapter there is a summary of the main conclusion of the key ideas discussed in the chapter. At the end of the thesis there is the general summary, list of sources and attachments.
The Interpretation of the Concept of Dominant Position in Competition Law
Keywords: Juridiskā zinātne